2020
DOI: 10.2147/ijgm.s263199
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Characteristics of <em>Acalypha indica</em> Poisoning</p>

Abstract: Background: Acalypha indica is a tropical plant used as a herbal medicine in various parts of the world, including Thailand. In glucose-6-phosphate dehydrogenase (G6PD)-deficient patients, acute hemolysis has been reported following the ingestion of this plant. Methemoglobinemia was reported in the present study. Patients and Methods: Descriptive data of patients who suffered from Acalypha indica toxicity reported from different hospitals to the Ramathibodi Poison Center were retrieved from 2011 to 2019. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Acute hemolysis with A. indica resulting in the subsequent discovery of G6PD deficiency was reported previously from South India, Sri Lanka, Malaysia, and Thailand, with most cases from Sri Lanka [ 2 , 3 , 7 12 ]. The majority of the reported patients were men.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Acute hemolysis with A. indica resulting in the subsequent discovery of G6PD deficiency was reported previously from South India, Sri Lanka, Malaysia, and Thailand, with most cases from Sri Lanka [ 2 , 3 , 7 12 ]. The majority of the reported patients were men.…”
Section: Discussionmentioning
confidence: 98%
“…A case series reported that symptoms of dark urine and jaundice develop as early as 15 min to 4 hour following consumption, however, the patients presented to the hospital after a delay of 2–4 days, with worsening haemolysis and acute kidney injury [ 2 ]. The only reported case of fatality due to A. indica -related haemolysis is of a 70-year-old male with premorbid chronic coronary artery and pulmonary disease [ 2 ]. Male sex, young age of presentation, no family history, fever, vomiting, and high alkaline phosphatase levels predict severe haemolysis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations